Eustachian Tube Function in Geriatric Subjects - H, Venkatesh Aithal (Journal of All India Institute of Speech and Hearing)
’What does "old age" mean? To a child of 4 years, a tall child of 12 years seems " old ", to a teenager, a worker,-aged 40 is "old".These are individuals who appear at a age of 50 years, to be ’old’ in regard to their activity, vitality and their state of health. On the other hand, there are individuals at th e age of 70 years who appear to be young in terms of their health, social activity and general vitality ’ (Hull, 1978). Therefore, ’ old age ’, then, is, indeed, arbitrarily defined.